2021
DOI: 10.1177/15357597211025408
|View full text |Cite
|
Sign up to set email alerts
|

Of Blobs and Buzzes: Does SISCOM Imaging Actually Help SEEG Planning?

Abstract: Perfusion patterns observed in Subtraction Ictal SPECT Co-registered to MRI (SISCOM) assist in focus localization and surgical planning for patients with medically intractable focal epilepsy. While the localizing value of SISCOM has been widely investigated, its relationship to the underlying electrophysiology has not been extensively studied and is therefore not well understood. In the present study, we set to investigate this relationship in a cohort of 70 consecutive patients who underwent ictal and interic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The complex hyperperfusion patterns unique to ictal SPECT reflect seizure onset and propagation pathways (Cleeren et al, 2016 ; Van Paesschen, 2004 ). We have previously shown that SPECT‐directed SEEG planning allows for a more complete electrographic sampling of salient areas, which in turn correlate with specific SEEG electrophysiological signals (power “fingerprints”) in the course of SEEG‐recorded seizures (Englot & Lagrange, 2022 ; Krishnan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complex hyperperfusion patterns unique to ictal SPECT reflect seizure onset and propagation pathways (Cleeren et al, 2016 ; Van Paesschen, 2004 ). We have previously shown that SPECT‐directed SEEG planning allows for a more complete electrographic sampling of salient areas, which in turn correlate with specific SEEG electrophysiological signals (power “fingerprints”) in the course of SEEG‐recorded seizures (Englot & Lagrange, 2022 ; Krishnan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%